2021
DOI: 10.1002/jcop.22742
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social support on work stress in health workers during the pandemic: The mediation role of resilience

Abstract: Stressful experiences commonly increase among health workers during the coronavirus disease 2019 (COVID‐19) pandemic. From this perspective, this study primarily aimed to examine the mediating role of resilience in the effect of perceived social support on work stress among health workers. The sample of the study consisted of 402 health workers. In the research, the “General Work Stress Scale,” “Brief Resiliency Scale,” and “Multidimensional Scale of Perceived Social Support” were used. There was a statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…The results of this study found that there was no significant relationship between work stress and social support. The results of this study support the results of previous research conducted by Kreh and Maiorano which explained that there is no significant effect between social support and stress in the work environment (Karadaş & Duran, 2022). On the other hand, this study contradicts previous research conducted by Setiawan in 2013 which stated that there was a significant influence between social support and work stress (Setiawan & Darminto, 2013).…”
Section: Resultssupporting
confidence: 72%
“…The results of this study found that there was no significant relationship between work stress and social support. The results of this study support the results of previous research conducted by Kreh and Maiorano which explained that there is no significant effect between social support and stress in the work environment (Karadaş & Duran, 2022). On the other hand, this study contradicts previous research conducted by Setiawan in 2013 which stated that there was a significant influence between social support and work stress (Setiawan & Darminto, 2013).…”
Section: Resultssupporting
confidence: 72%
“…On the other hand, it was found that resilience at work partially mediated the influences of HPWS on thriving at work and job burnout, yet, in different directions. In a nurse-focused study, although the literature has reported that resilience at work can enhance positive employee outcomes [ 22 , 23 , 24 ] and reduce negative employee outcomes [ 21 , 23 ], there has been no research to explore and test whether HPWS can impact employee outcomes through developing resilience at work. Our research filled this gap.…”
Section: Discussionmentioning
confidence: 99%
“…To cope with nurses’ stresses and burnout, healthcare organizations are suggested to frequently support nurses in thriving at work in China [ 18 , 19 , 20 ]. A nurse’s resilience has been reported to reduce negative employee outcomes, such as work stress [ 21 ], job insecurity [ 22 ], and turnover intention [ 23 ], while enhancing positive outcomes, such as proactive work behavior [ 24 ], perceived justice, trust in the organization, creative performance [ 22 ], job satisfaction, quality of care [ 23 ]. Furthermore, HRM systems have also been argued and reported to enhance positive and reduce negative employee outcomes [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, social support is positively associated with job satisfaction (59). Social support and work stress were negatively correlated, and the reinforcement of social support can reduce the work stress of medical workers (60). The job satisfaction of medical staff not only has a direct negative impact on turnover intention, but also has an indirect impact on turnover intention through work engagement (61).…”
Section: Job Satisfaction With the Work Of The Clinical Laboratorymentioning
confidence: 99%